The Influence of Digital Marketing Capability on the Marketing Performance of MSMEs in the Digital Transformation Era: The Moderating Role of Customer Satisfaction - Mulyono, Sri; Ramadani, Ika (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
Digital transformation has reshaped marketing practices, requiring MSMEs to strengthen their digital marketing capability to remain competitive. Variations in marketing performance among digitally active MSMEs suggest the presence of additional influencing factors beyond technological competence. This study aims to examine the influence of digital marketing capability on the marketing performance of MSMEs and to analyze the moderating role of customer satisfaction in this relationship. A quantitative explanatory survey was conducted involving 120 MSME actors implementing digital marketing strategies. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression and Moderated Regression Analysis (MRA) to test direct and interaction effects. Findings reveal that digital marketing capability significantly enhances marketing performance. Customer satisfaction also has a direct positive effect and significantly strengthens the relationship between digital marketing capability and marketing performance. The interaction effect indicates that higher customer satisfaction amplifies the positive impact of digital capability on business outcomes. The study concludes that optimal MSME marketing performance in the digital era depends on the integration of digital capability and customer satisfaction management. The novelty lies in positioning customer satisfaction as a moderating variable rather than solely as an outcome, providing both conceptual and methodological contributions to digital marketing research in the MSME context.